The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.2147/idr.s233694
|View full text |Cite
|
Sign up to set email alerts
|

<p>Virulence Constitution of Multi-Drug-Resistant <em>Pseudomonas aeruginosa</em> in Upper Egypt</p>

Abstract: Ventilator-associated pneumonia caused by Pseudomonas aeruginosa (P. aeruginosa) is a major health-care problem. In this study, we explored the epidemiology of virulence determinants among multi-drug-resistant (MDR) clinical P. aeruginosa isolates from hospitalized patients with ventilator-associated pneumonia in intensive care units in Upper Egypt. Patients and Methods: MDR P. aeruginosa isolates were screened for the presence of eight virulence factors and typed by ERIC-PCR. Results: A total of 39 clinical M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 37 publications
4
15
2
Order By: Relevance
“…The algD gene was detected in 98.1% of isolates, while absence of algU was noted in more than 53.0%. These findings differ from those reported by Hassuna et al (2020) [1] and Fazeli et al (2014) [57], who observed higher frequencies for algU and lower frequencies for algD, respectively. As both genes encode fundamental proteins for alginate biosynthesis, functioning as one of its main adhesins and mainly found in the respiratory tract of patients with acute infections and cystic fibrosis (CF), the low frequency of the algU may be associated to the high frequency of non-RTI isolates (57.4%) and also indicate deficient alginate production by most of tested isolates [10,58].…”
Section: Plos Onecontrasting
confidence: 94%
See 4 more Smart Citations
“…The algD gene was detected in 98.1% of isolates, while absence of algU was noted in more than 53.0%. These findings differ from those reported by Hassuna et al (2020) [1] and Fazeli et al (2014) [57], who observed higher frequencies for algU and lower frequencies for algD, respectively. As both genes encode fundamental proteins for alginate biosynthesis, functioning as one of its main adhesins and mainly found in the respiratory tract of patients with acute infections and cystic fibrosis (CF), the low frequency of the algU may be associated to the high frequency of non-RTI isolates (57.4%) and also indicate deficient alginate production by most of tested isolates [10,58].…”
Section: Plos Onecontrasting
confidence: 94%
“…The high prevalence of the aprA gene is in line with other studies [1,13,56,59], highlighting the importance of zinc-metalloprotease secreted by T1SS, which has functions related to invasion, causing collagen and fibrinogen degradation in synergy with T2SS elastases, and…”
Section: Plos Onesupporting
confidence: 87%
See 3 more Smart Citations